Terminally modified, short phosphorothioate oligonucleotides as inhibitors of gene expression in cells - Marzenell, Paul David; Hagen, Helen; Blechinger, Jenny; Erfle, Holger; Mokhir, Andriy (Bioorganic & medicinal chemistry letters, 2014)
Phosphorothioates are excellent antisense inhibitors, which are active both in cells and in vivo. Since their affinity to complementary ribonucleic acids is rather low, long strands (⩾20-mers) are typically required to achieve the desired biological activity. However, mismatch discrimination of long inhibitors is reduced. In contrast, shorter phosphorothioates exhibit better sequence specificity, but have in most cases too low affinity for practical applications in cells. We screened a range of terminal modifiers of a 14-mer phosphorothioate sequence, which is complementary to mRNA of a representative gene, whose protein product is fluorescent (DsRed2) and easy to monitor in cells. We found that optimal combinations of 5′- and 3′-modifications include 5′-trimethoxystilbene with 3′-uracil(anthraquinone)-cap, 5′-chloic acid derivative with 3′-uracyl(anthraquinone)-cap and 5′-cholic acid derivative with three 3′-LNA moieties. In contrast to the LNA, stabilizing and activity-enhancing effects of other mentioned modifiers for PTO/RNA duplexes have not been previously reported. We observed that the 14-mer inhibitor carrying 5′-cholic acid derivative with three 3′-LNA moieties inhibits expression of DsRed2 in cells stronger than the unmodified 21-mer. Mismatch discrimination of this inhibitor was found to be comparable to that of the unmodified 14-mer.
Gesehen am 21.07.2020